2012
DOI: 10.1080/14786419.2011.566870
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterisation and cytotoxicity study of arjunolic acid fromTerminalia arjuna

Abstract: Arjunolic acid (AA), a triterpenoid, was isolated from the ethyl acetate and methanol extracts of Terminalia arjuna core wood. The purity of AA was analysed by its melting point, FT-IR and NMR spectroscopy analyses. In vitro cytotoxicity was assessed using Ehrlich ascites carcinoma (EAC) and Dalton's lymphoma (DAL) cell lines by incubating with different concentrations of AA. The cancer cell death percentage at 100 µg concentrations of AA ranged between 66% and 70% on the DAL and EAC cell lines, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Fourier transform infrared spectroscopy (FTIR) analysis-FTIR spectrum of AA supported previous reports (14) showing characteristic -OH, C-H, and CϭO stretches at 3467, 2927, and 1708 cm Ϫ1 positions, respectively. Characteristic C-O stretching vibrations were also obtained at 475, 598, 1042, and 1456 cm Ϫ1 .…”
Section: Aa Directly Interacts With Ppar␣supporting
confidence: 84%
See 1 more Smart Citation
“…Fourier transform infrared spectroscopy (FTIR) analysis-FTIR spectrum of AA supported previous reports (14) showing characteristic -OH, C-H, and CϭO stretches at 3467, 2927, and 1708 cm Ϫ1 positions, respectively. Characteristic C-O stretching vibrations were also obtained at 475, 598, 1042, and 1456 cm Ϫ1 .…”
Section: Aa Directly Interacts With Ppar␣supporting
confidence: 84%
“…Thus, the objective of our study was to look into the effect of AA, which is purified and crystallized from ethyl acetate and methanol extracts of the corewood of arjuna plant (14) on cardiac hypertrophy-associated fibrosis, and to seek out its plausible mechanism of action on fibrotic signaling through identification of its specific molecular target.…”
mentioning
confidence: 99%
“…Preliminary anti-tumor activity screening study found that the EtOAc and CHCl3 fractions from the EtOH extract of GHJ showed significant anti-tumor activities [7] and seventeen compounds including dammarane-type, oleanane-and ursane-type were isolated and identified ( Figure 1). These included 20(S)-hydroxydammar-24-en-3-one (1) [8], 20(S)-protopanaxadiol-3-one (2) [9], 20(S),24(R)-dihydroxydammaran-25-en-3-one (3) [10], 20(S),24(S)-dihydroxydammaran-25-en-3-one (4) [10], 1β,12β,20(S)-trihydroxydammar-24-en-3-one (5) [11], 12β,20(R),24(R)-trihydroxydammar-25-en-3-one (6), 20(S)-protopanaxadiol (7) [12], 1β,3α,12β,20(S)-tetrol-24-ene-dammar (8) [11], oleanolic acid (9) [13], 3-epikatonic acid (10) [14], 2α-hydroxyoleanolic acid (11) [13], 2α,3β,23-trihydroxyolean-12-en-28-oic acid (12) [15], ursolic acid (13) [16], 3β-hydroxyurs-20-en-28-oic acid (14) [17], 2α-hydroxyursolic acid (15) [13], 3-oxo-23-hydroxyurs-12-en-28-oic acid (16) [18], 2α,3β,23-trihydroxyurs-12-en-28-oic acid (17) [19]. Among of them, dammarane-type triterpenoids were isolated for the first time from the Juglans genus and a new dammarane triterpene 6 was isolated and its structure elucidated by 1D-, 2D-NMR spectroscopy, HR-ESI-MS and Mosher's method.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of anticancer phytoconstituents from T. arjuna stem bark were carried out in various ways, such as maceration extraction [], reflux, and soxhlet extraction []. However, these conventional extraction methods are usually time and solvent consuming.…”
Section: Introductionmentioning
confidence: 99%